Viewing "Aesthetic Freedom" from a Modern Perspective: A Review of Schiller’s "A Brief Book of Aesthetic Education - Zeng, Qingqin (Journal of Theory and Practice of Social Science, 2023)
The "Brief Book of Aesthetic Education" is known as the "first manifesto of aesthetic education". The author believes that the reason why Schiller affirmed beauty is because beauty is the second creator of humanity; Beauty can redeem a person's soul; Beauty endows people with freedom. Schiller proposed the concept of "aesthetic education", which I believe is due to the alienation of complex human nature, the need for progress and development of the times, and its role as a mediator between emotional and rational impulses. Schiller's aesthetic education ideas also provide us with certain inspiration for modern people. We need aesthetic education to enhance the spiritual temperament of the entire human society, bridge the alienation of human nature, and seek rational freedom.